The Role of Communication Media in Improving Students Achievement at Faculty of Da'wah and Communication, IAI Al-Aziziyah Samalanga Bireuen Aceh - Saiful Bahri (Britain International for Academic Research (BIAR) Publisher, 2020)
The focus of this study is the role of communication media in improving students achievement at Faculty of Da'wa and Communication, Al-Aziziyah Samalanga. To answer the focus of the study thoroughly and in depth, in this study used a descriptive qualitative research method that is useful to provide facts and data about the communication media of students at Faculty of Da'wah and Communication, IAI Al-Aziziyah. The data obtained were analyzed using the theory of usage and satisfaction in order to obtain several activities when communicating. From the results of the study it was found that: (1) communication media used by students of Da'wah and communication Faculty, IAI Al-Aziziyah namely books, newspapers, magazines, television, BBM, Line, Whatsapp, Facebook, Youtube and kompas.com (2) the way how to use media student communication of Da'wah and Communication Faculty, IAI Al-Aziziyah namely; join the Whatsapp, BBM, Line group with the aim of exchanging information between friends, faculty, or even between campuses, watching the training videos related to lectures, following a kind of toefl school on Facebook. The role of the communication media in improving the achievements of students of Faculty of Da'wah and Communication, Al-Aziziyah Samalanga is to make it easier for them to look for references because wherever and whenever they can access them. So as to shorten and save time and place.